Perubahan perilaku kader dalam upaya peningkatan pengetahuan dan sikap wanita usia Subur (WUS) tentang ASI-eksklusif di desa Talang Mulya Lampung - Wahid Tri Wahyudi; Nita Evrianasari (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
Knowledge and attitude towards exclusive breastfeeding among women of childbearing age and empowerment by health worker cadresBackground: Health worker cadres are one of the frontline maternal and child health service providers, they are have an important role in empowering the community and providing convenience to the community in obtaining basic health services because they are the ones who best understand the conditions of the community's needs in the region. At Talang Mulya Village, they are have not had a significant influence on changes in public health behavior, especially in exclusive breastfeeding extension services they need more a adequate knowledge and skills.Purpose: Knowing changing in knowledge and attitude towards exclusive breastfeeding among women of childbearing age and empowerment by health worker cadresMethod: Quantitative research with the research design